2003
DOI: 10.1046/j.1365-2842.2003.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of war stress on the prevalence of signs and symptoms of temporomandibular disorders

Abstract: The aim of this study was to determine the prevalence of signs and symptoms of temporomandibular disorders in patients with post-traumatic stress disorder (PTSD) occurring as a consequence of exposure to war stress. The examined group consisted of 100 male subjects, aged from 25 to 50 years, who had taken part in the War in Croatia, and in whom PTSD had previously been diagnosed. The control group comprised 100 subjects, without PTSD, of the same sex and age group, who had not taken part in the War. A function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
17

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 20 publications
2
25
0
17
Order By: Relevance
“…[1718] These results are agreement with the present study showed that TMJD as a common symptom of TMDs is more prevalent in war veterans’ patients with PTSD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[1718] These results are agreement with the present study showed that TMJD as a common symptom of TMDs is more prevalent in war veterans’ patients with PTSD.…”
Section: Discussionsupporting
confidence: 92%
“…(2003)[18] showed that 82% of the subjects with PTSD had symptoms of dysfunction compared with 24% of the subjects in the healthy control group. This was less than present study with 36.7% of the patients with PTSD compared with 13.3 to 40% of the subjects in the healthy control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varios estudios a nivel mundial determinaron que la prevalencia del estrés tiene un porcentaje que va desde el 23,3% al 82% tanto en hombres y mujeres (12)(13)(14). Apostolo et al, en el 2006 realizaron un estudio descriptivo en 192 sujetos analizando el índice DASS 21 con una prevalencia del 50% principalmente en mujeres(15), datos que revelan una correlación directa con la muestra obtenida.…”
Section: Tabla 2 Prevalencia De Estrés Emocionalunclassified
“…A majority of conceptions thus far point to malocclusion or stressborne dysfunction of the masticatory muscles as representing the onset of TMJ pathology (Laskin, 1993;Le Resche, 1997;Ahlberg et al, 2002;Uhac et al, 2003). More recent conceptions accept that micro-or macroinjuries, which affect the joint directly or indirectly, are the predominant aetiological factors in TMJ disorders.…”
Section: Introductionmentioning
confidence: 99%